Socio-affective development and its influence on school performance in primary school: an occupational therapy perspective (Cuidado y Ocupación Humana, 2024)
Objetive: Socio-affective development has been an area of research interest in the area of health, which is why different researchers have dedicated efforts to understanding its impact on the academic performance and well-being of children. In this review, multiple articles have been analyzed that have concluded that this aspect not only affects school performance, but also the experience and integrity of students.Taking the above into account, it addresses the interrelationship between the impact of socio-affective development in childhood and its influence on academic performance, with a special focus on the role of Occupational Therapy in the school environment. To understand this phenomenon, it is essential to define the concept of socio-affective development, which includes the ability to manage emotions and establish positive relationships.According to Piaget (1982), the development of social skills begins with the child's first interactions with his environment. These skills, according to the review carried out, are essential for their social adaptation and comprehensive development. Throughout the article it will be mentioned how occupational therapy can play a crucial role in strengthening these skills in the school environment, creating an environment conducive to optimal learning and development of students.
Keywords: Development; Academic performance; Socio-affective; Skills; Emotions; Affective relationships; Childhood; Primary; Strategies; Occupational Therapy